ePortfolios as a platform for evidencing employability and building professional identity: A literature review - Carter, Stacey (2021)
This paper reviews the theoretical background and contextualized application of ePortfolios in tertiary education. Higher education graduates are expected to provide evidence demonstrating a complex skill set as they transition to employment, and ePortfolios are a potential tool with which to do this. This literature review explores current understanding and contemporary practices for how ePortfolios can be curated to demonstrate student competency in the desired skills. It also considers how to choose between ePortfolio platforms and how ePortfolio outputs are designed and structured to align student learning outcomes and associated evidence of student ability with student professional identity, using Australian nursing/midwifery and engineering discipline case studies to identify relevant industry-based skills as examples. While the typology of ePortfolios is consistently recognized, the implementation in teaching varies across contexts. When integrating ePortfolios into the curriculum, many elements must be addressed, including assessment strategies, pedagogical approaches, integration of professional identity, and resourcing.